Diagnostic value of signs, symptoms and diagnostic tests for diagnosing pneumonia in ambulant children in developed countries: a systematic review. (December 2018) - Schot, Marjolein; Dekker, Anne; Giorgi, Wesley; Hopstaken, Rogier; Wit, Niek; Verheij, Theo; Cals, Jochen
Abstract Identifying a child with pneumonia in the large group of children with acute respiratory tract infections can be challenging for primary care physicians. Knowledge on the diagnostic value of specific signs and symptoms may guide future decision rules and guidelines for clinicians. We aimed to identify and systematically review available evidence for the diagnostic value of signs, symptoms, and additional tests to diagnose pneumonia in children in an ambulatory setting in developed countries. We conducted a systematic review, searching in the electronic databases of PubMed and Embase. Quality assessment of studies was done using the QUADAS-2 criteria. After data extraction from selected studies, we calculated and summarized test characteristics (sensitivity, specificity, negative and positive predictive values) of all available signs, symptoms, additional laboratory tests, and chest ultrasonography. The original search yielded 4665 records, of which 17 articles were eligible for analysis: 12 studies on signs and symptoms, 4 on additional laboratory tests, and 6 on ultrasonography. All included studies were performed in a secondary care setting. Risk of bias was present in the majority of studies in the domain of patient selection. Prevalence of pneumonia varied from 3.4% to 71.7%. The diagnostic value of the available 27 individual signs and symptoms to identify pneumonia was low. In a low prevalence setting, (4 studies, pneumonia prevalence <10%) clinically ill appearance of the child and oxygen saturation <94% can aid a physician. In a high prevalence setting (10 studies, pneumonia >10%), additional diagnostic tests such as oxygen saturation, C-reactive protein, and white blood cell count are more promising. Chest ultrasonography showed high diagnostic value in settings with higher prevalence of pneumonia. Single signs and symptoms from medical history and physical examination or individual additional diagnostic tests are insufficient to diagnose pneumonia in ambulant children. Very few diagnostic studies are conducted in settings with low prevalence of pneumonia. Future research in low prevalence settings should focus on the diagnostic value of the combination of clinical features and additional testing possibly using meta-analysis of individual data.